The Effect of Cash Holding and Financial Regulation on Bankruptcy Risk: Evidence from Cross-Country Banking Industry - Prasojo Prasojo; Tettet Fitrijanti; Nunuy Nur Afiah (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, 2025)
This paper studies the determinants of bank financial distress using a 2012–2018 multi-country panel (73,124 bank-year observations; 10,562 banks; 32 countries). Fixed-effects estimates show that higher capital (Tier-1/RWA) and better asset quality (lower NPL) are associated with higher Z-scores (lower distress). Intangible intensity is positively related to distress. Cash-holding proxies load negatively in the Z-score equation, indicating that larger cash balances coincide with lower Z-scores in this sample. One interpretation is that excess cash reflects under-deployment or precautionary hoarding during adverse conditions, which does not translate into stronger stability. Results are robust to alternative specifications. Policy implications highlight calibrating core capital, strengthening credit risk management, and optimizing not hoarding liquidity.